2014
DOI: 10.3386/w20261
|View full text |Cite
|
Sign up to set email alerts
|

The Runner-Up Effect

Abstract: Exploiting regression discontinuity designs in Brazilian, Indian, and Canadian first-past-the-post elections, we document that second-place candidates are substantially more likely than close third-place candidates to run in, and win, subsequent elections. Since both candidates lost the election and had similar electoral performance, this is the effect of being labeled the runner-up. We explore the potential mechanisms for this runner-up effect, including selection into candidacy, heuristic behavior by politic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…At a general level, this finding is reminiscent of a recent branch of voting theory, in which votes can have a downstream signaling effect on policy (Meirowitz and Shotts 2009; Piketty 2000; Razin 2003). It is also in line with the empirical findings of Anagol and Fujiwara (2014) that finishing second instead of third in plurality elections affects a candidate's future political success.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At a general level, this finding is reminiscent of a recent branch of voting theory, in which votes can have a downstream signaling effect on policy (Meirowitz and Shotts 2009; Piketty 2000; Razin 2003). It is also in line with the empirical findings of Anagol and Fujiwara (2014) that finishing second instead of third in plurality elections affects a candidate's future political success.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, this accords well with our reasoning that the key mechanism generating the primary effect is found at the party level (in promotion decisions) rather than at the candidate level (for example, via higher career ambitions and efforts). Furthermore, it testifies to the fact that party allegiances are quite weak in the Brazilian municipalities, where party switching is commonplace (Anagol and Fujiwara 2014). For example, a candidate who fails to gain the nomination in his or her own party can simply switch to another party.…”
Section: Background Data and Results For Brazilmentioning
confidence: 87%
“…Additionally, by focusing on parties that almost tied in votes, our results indicate that agents respond to rankings that provide no additional information conditional on the publicly available variable that fully determines the ranking (votes). This adds to evidence of rank-based decision-making in politics (Anagol and Fujiwara 2016;Folke, Persson, and Rickne 2016;Meriläinen and Tukiainen 2018;Pons and Tricaud 2018) and is consistent with models where agents make choices over-weighting salient attributes (Bordalo, Gennaioli, and Shleifer 2013). Our results thus speak to how narrow victories are interpreted (or marketed) by some as "the will of the people."…”
Section: Introductionsupporting
confidence: 84%
“…Consistent with Myatt 's ( ) prediction that the amount of strategic voting increases with the level of information, Hall and Snyder () found that higher levels of information in U.S. primary elections decrease the number of votes and donations “wasted” on candidates unlikely to win. An important piece of information used by voters to coordinate comes from candidates' rankings in previous elections: second‐place candidates are substantially more likely than close third‐place candidates to run in, and win, a subsequent election ( Anagol and Fujiwara ()).…”
Section: Introductionmentioning
confidence: 99%